User experience evaluation towards interface design of digital footprint awareness application - Tengku Siti Meriam Tengku Wook,; Hazura Mohamed,; Noraidah Sahari@Ashaari,; Siti Fadzilah Mat Noor,; Zurina Muda,; Intan Yusrina Zairon,; Firas Layth Khaleel, (Penerbit Universiti Kebangsaan Malaysia, 2020)
User experience (UX) towards designs of an application or product affects the way such user receives the product. UX also becomes increasingly crucial as users obtain a rating of downloaded app experience that may affect sales and improve the application performance expectations. This study aims to evaluate user experience in order to validate user needs on digital footprint awareness applications that have been developed through the triangulation technique that involves three user experience testing methods which are guessability, think aloud and observation to acquire feedback and suggestions from experts and end users for the application development. The findings indicate that an important aspect of user satisfaction within this app is the use of attractive colours, clear and appropriate texts and clear and systematic guidelines to reduce the user's cognitive strains. In addition, the emphasis is on enhancing the fun, entertaining and interface design based on using different perspectives of its use in fun, motivational challenges and skills to enhance the application usability and learning ability.